Effect of Apical Pinching and Growth Retardants on Seed Quality Parameters of Okra (Abelmoschus esculentus (L.) Moench.) cv. GO-6 - DS DESHMUKH; CA BABARIYA; MJ JADAV; JB PATEL; PG MANDOD (Seed Research, 2026)
The investigation was undertaken at the Sagdividi Farm, Department of Seed Science and Technology, College of Agriculture, Junagadh Agricultural University, Junagadh, during kharif 2021 to study the effect of apical pinching and growth retardants on seed quality parameter of okra (Abelmoschus esculentus (L.) Moench.) cv. GO-6. Based on overall results, it was found that apical pinching and growth retardant played an important role on seed quality parameters of okra. Pinching at 20 DAS (P1) was found effective in improving quality of seeds of okra. The maximum improvement was observed for all the seed quality parameters except hundred seed weight and seed diameter with application of KH2PO4 @ 5000 ppm.